2011
DOI: 10.1007/s11033-011-1299-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of MTHFR gene SNPs C677T and A1298C: a study among 23 population groups of India

Abstract: Elevated homocysteine is a risk factor for many complex disorders. The role of methylenetetrahydrofolate reductase (MTHFR) gene in methylation of homocysteine makes it one of the most important candidate genes for these disorders. Considering the heterogeneity in its distribution in world populations, we screened MTHFR C677T and A1298C single nucleotide polymorphisms in a total of 23 Indian caste, tribal and religious population groups from five geographical regions of India and belonging to four major linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
3
28
1
2
Order By: Relevance
“…Weisberg et al [7] detected 1 child with spina bifida who carried TT/AC genotype; a meta-analysis of 22 studies with 12,647 subjects found 31 individuals (0.25%) with the CT/CC genotype, 58 (0.46%) with the TT/AC genotype, 4 four (0.03%) with the TT/CC genotype [28] ; the most recent study conducted in India observed that the frequency of TT/AC genotype plus CT/CC genotype was 0.94%, and the 677T-1298C haplotype frequencies ranged from 1.2% to 3.6% in different population groups. [17] In this study, we observed that 51 individuals were the CT/CC genotype, 92 were the TT/AC genotype, 17 were TT/CC genotype, and that the frequency of 677T-1298C haplotype was 0.9%. These findings indicate that although the MTHFR C677T and A1298C polymorphisms are usually in trans , they are occasionally in cis configurations, and indicate that the 2 polymorphisms are at incomplete LD, which is further substanticated by a formal LD test in our study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Weisberg et al [7] detected 1 child with spina bifida who carried TT/AC genotype; a meta-analysis of 22 studies with 12,647 subjects found 31 individuals (0.25%) with the CT/CC genotype, 58 (0.46%) with the TT/AC genotype, 4 four (0.03%) with the TT/CC genotype [28] ; the most recent study conducted in India observed that the frequency of TT/AC genotype plus CT/CC genotype was 0.94%, and the 677T-1298C haplotype frequencies ranged from 1.2% to 3.6% in different population groups. [17] In this study, we observed that 51 individuals were the CT/CC genotype, 92 were the TT/AC genotype, 17 were TT/CC genotype, and that the frequency of 677T-1298C haplotype was 0.9%. These findings indicate that although the MTHFR C677T and A1298C polymorphisms are usually in trans , they are occasionally in cis configurations, and indicate that the 2 polymorphisms are at incomplete LD, which is further substanticated by a formal LD test in our study.…”
Section: Discussionmentioning
confidence: 70%
“…[17,27,28] Among these common combined genotypes, the CT/AC genotype received the most attention because it was associated with lower enzyme activity and higher plasma Hcy concentrations than heterozygosity for either variant. [7,8,29] The mean frequency of the CT/AC genotype in our study was 13.7%, which is similar to that of Mexicans, but lower than that of Turks, French, and Italians, and higher than that of Africans.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study among Gaddis, T-allele frequency is 18%, which is next to the highest frequency observed in the north Indian population, viz. 23% among Sindhi (Saraswathy et al, 2011). This high frequency of T-allele among Gaddis could be attributed to three major reasons; gene flow, mating pattern and selection.…”
Section: Resultsmentioning
confidence: 94%
“…Migration, settlements and colonization might have helped in spreading this allele to other regions. According to a study by Saraswathy et al (2011), the average frequency among five north Indian populations is found to be 16.74%, while that of four south Indian populations is 7.57%. As seen, the average frequency in the south Indian population is clearly half of the north Indian populations, showing a north-to-south gradient of T-allele in India.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation